2020
DOI: 10.1101/2020.04.17.046730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune-challenged vampire bats produce fewer contact calls

Abstract: 27Infections can affect how animals vocalize and, hence, interact with conspecifics. While this effect has 28 been shown for mate-attraction calls, other vocalizations that facilitate social contact have received less 29 attention. When isolated, vampire bats produce contact calls which attract highly associated groupmates. 30Here, we test the effect of an immune challenge on contact calling rates of individually isolated vampire 31 bats. Sickness behavior did not appear to change call structure, but it decrea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…work in two other mammalian systems found that infected individuals (or those expressing sickness behaviours) are less likely than control individuals to engage in affiliative allogrooming with conspecifics [banded mongooses (Mungos mungo), Fairbanks et al, 2014; vampire bats (Desmodus rotundus), Stockmaier et al, 2018]. In vampire bats, these changes in allogrooming during sickness behaviour expression, potentially in combination with reduced contact calling (Stockmaier et al, 2020a), result in significant reductions in several measures of social connectedness relative to controls (Ripperger et al, 2020). Overall, host-mediated reductions in social interactions during infection, particularly when they occur during the host's infectious period, likely reduce transmission of socially transmitted parasites.…”
Section: Parasite Infection Influences Host Social Behaviours (Arrow B)mentioning
confidence: 99%
“…work in two other mammalian systems found that infected individuals (or those expressing sickness behaviours) are less likely than control individuals to engage in affiliative allogrooming with conspecifics [banded mongooses (Mungos mungo), Fairbanks et al, 2014; vampire bats (Desmodus rotundus), Stockmaier et al, 2018]. In vampire bats, these changes in allogrooming during sickness behaviour expression, potentially in combination with reduced contact calling (Stockmaier et al, 2020a), result in significant reductions in several measures of social connectedness relative to controls (Ripperger et al, 2020). Overall, host-mediated reductions in social interactions during infection, particularly when they occur during the host's infectious period, likely reduce transmission of socially transmitted parasites.…”
Section: Parasite Infection Influences Host Social Behaviours (Arrow B)mentioning
confidence: 99%